MENINGKATKAN HASIL BELAJAR IPS TENTANG AKTIVITAS EKONOMI DAN SUMBER DAYA ALAM MELALUI MODEL PICTURE AND PICTURE - sudrajat, ajat; sari, elvi yusmika (Jurnal Pendidikan Progresif, 2016)
Improving Social Science LearningOutcomes of Economy Activity and Natural Resources Through Picture and Picture. The purpose of this study was to improve the learning outcomes of IPS about the activities and natural resources through a model picture and picture in the fourth grade of SDN 09 Pagi Rawamangun, Pulogadung in East Jakarta. The research wasconducted at SDN Rawamangun 09 Pagi, which is located at Jalan Pemuda No.06 Jakarta Sub Rawamangun Kec.Pulogadung Timur. The study was conducted during one month, in January 2016 in the 2nd half of the school year 2015-2016. This research method was using classroom action research cycle model of Stephen Kemmis and Mc. Taggart with 4 stages of each cycle including planning, implementation, observation and reflection. The research shows the data obtained from the learning process in improving student learning outcomes using the model picture and picture. 55.17% in the first cycle, the second cycle of 89.65%, thus the model picture and picture can improve student learning outcomes Keywords: social studies results, picture and picture model, economy activity and natural resources DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601